Positive electrode active material for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery
The development of a lithium transition metal composite oxide positive electrode active material with high Ni content and specific polygonal particle shapes addresses the issue of particle cracking in nonaqueous electrolyte secondary batteries, enhancing durability and cycle performance.
Patent Information
- Application Number
- JP2022517533
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-28
- Filing Date
- 2021-03-09
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2041-03-09
AI Technical Summary
Nonaqueous electrolyte secondary batteries face challenges with particle cracking of positive electrode active materials during charging and discharging, leading to decreased battery capacity and durability.
A positive electrode active material composed of lithium transition metal composite oxide with 85 mol % or more Ni content, featuring single particles and secondary particles with specific polygonal cross-sectional shapes, is developed to reduce particle cracking and enhance durability.
The proposed positive electrode active material significantly reduces particle cracking, resulting in high capacity retention and excellent cycle characteristics for nonaqueous electrolyte secondary batteries.
Smart Images

Figure 0007664545000002 
Figure 0007664545000003 
Figure 0007664545000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a positive electrode active material for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery using the positive electrode active material. [Background technology]
[0002] In non-aqueous electrolyte secondary batteries such as lithium ion batteries, the positive electrode active material has a significant effect on battery performance such as input / output characteristics, capacity, and cycle characteristics. Generally, lithium transition metal composite oxides containing metal elements such as Ni, Co, Mn, and Al and composed of secondary particles formed by aggregation of primary particles are used as positive electrode active materials. Since the properties of positive electrode active materials vary greatly depending on their composition, particle shape, etc., many studies have been conducted on various positive electrode active materials.
[0003] For example, Patent Document 1 discloses a positive electrode active material made of a lithium nickel cobalt manganese composite oxide that is composed of spherical or near-spherical primary single crystal particles and a small amount of secondary aggregate particles, in which the primary single crystal particles have a particle size of 0.5 to 10 μm and the cumulative percentage of particles having a particle size of 5 μm or less exceeds 60%. Patent Document 1 describes that the use of this positive electrode active material improves the high temperature stability, high voltage cycle characteristics, and safety of the battery. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-45998 A Summary of the Invention
[0005] It is known that in non-aqueous electrolyte secondary batteries, particle cracking occurs in the positive electrode active material during charging and discharging. When particle cracking occurs in the positive electrode active material, for example, the number of particles isolated from the conductive path in the positive electrode increases, leading to a decrease in battery capacity. For this reason, there is a demand for a positive electrode active material that is less susceptible to particle cracking and has high durability.
[0006] A positive electrode active material for a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure is composed of at least one of a single particle of a lithium transition metal composite oxide containing 85 mol % or more of Ni relative to the total molar amount of metal elements excluding Li, and a secondary particle including 10 or less primary particles, wherein the cross section of the single particle and the primary particle has a polygonal shape including sides with lengths of 1.5 μm or more, and at least three interior angles of the polygon are 45 to 160°.
[0007] A non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a positive electrode having a positive electrode core and a positive electrode mixture layer including the positive electrode active material provided on a surface of the positive electrode core, a negative electrode, and a non-aqueous electrolyte, and the positive electrode mixture layer has a BET specific surface area of 2.6 m before charge and discharge. 2 / g or less.
[0008] The positive electrode active material for a non-aqueous electrolyte secondary battery according to the present disclosure is less susceptible to particle cracking during charging and discharging and has excellent durability. Furthermore, a non-aqueous electrolyte secondary battery using the positive electrode active material according to the present disclosure has, for example, a high capacity retention rate after charge-discharge cycles and excellent cycle characteristics. [Brief description of the drawings]
[0009] [Figure 1] 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery according to an embodiment; [Diagram 2] FIG. 2 is a diagram illustrating a cross section of a particle of a positive electrode active material according to an embodiment of the present invention. [Diagram 3] 1 is a cross-sectional SEM image of a positive electrode mixture layer according to an example of an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] As described above, suppressing particle cracking of the positive electrode active material that may occur with charging and discharging is an important issue in improving battery performance such as cycle characteristics. As a result of intensive research by the present inventors to develop a positive electrode active material that is less likely to cause particle cracking and has high durability, the present inventors have succeeded in synthesizing a lithium transition metal composite oxide with a high Ni content, which is composed of at least one of single particles and secondary particles containing 10 or less primary particles, and the cross sections of the single particles and primary particles have a specific polygonal shape. The positive electrode active material made of this composite oxide has higher durability than conventional positive electrode active materials, and greatly contributes to improving the cycle characteristics of the battery.
[0011] Hereinafter, with reference to the drawings, an example of an embodiment of a positive electrode active material for a nonaqueous electrolyte secondary battery according to the present disclosure and a nonaqueous electrolyte secondary battery using the positive electrode active material will be described in detail. Note that it is initially assumed that the multiple embodiments and modified examples described below will be selectively combined.
[0012] In the following, a cylindrical battery in which a wound electrode body 14 is housed in a cylindrical exterior can 16 with a bottom is exemplified, but the exterior body of the battery is not limited to a cylindrical exterior can, and may be, for example, a square exterior can (square battery) or a coin-shaped exterior can (coin battery), or may be an exterior body (laminated battery) made of a laminate sheet including a metal layer and a resin layer. The electrode body may also be a laminated type electrode body in which multiple positive electrodes and multiple negative electrodes are alternately laminated with separators between them.
[0013] FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 according to an embodiment. As shown in FIG. 1, the nonaqueous electrolyte secondary battery 10 includes a wound electrode assembly 14, a nonaqueous electrolyte, and an exterior can 16 that accommodates the electrode assembly 14 and the nonaqueous electrolyte. The electrode assembly 14 has a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The exterior can 16 is a cylindrical metal container with a bottom that is open on one axial side, and the opening of the exterior can 16 is closed by a sealing body 17. In the following description, for convenience of explanation, the sealing body 17 side of the battery is referred to as the top, and the bottom side of the exterior can 16 is referred to as the bottom.
[0014] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. Examples of the non-aqueous solvent include esters, ethers, nitriles, amides, and mixed solvents of two or more of these. The non-aqueous solvent may contain a halogen-substituted compound in which at least a portion of the hydrogen of these solvents is replaced with a halogen atom such as fluorine. The electrolyte salt may include, for example, LiPF 6 The non-aqueous electrolyte is not limited to a liquid electrolyte, and may be a solid electrolyte.
[0015] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, and are alternately stacked in the radial direction of the electrode body 14 by being wound in a spiral shape. The negative electrode 12 is formed to be slightly larger than the positive electrode 11 in order to prevent lithium deposition. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in the longitudinal direction and the width direction (short direction). The two separators 13 are formed to be at least slightly larger than the positive electrode 11, and are arranged to sandwich the positive electrode 11, for example. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.
[0016] Insulating plates 18 and 19 are disposed above and below the electrode body 14. In the example shown in Fig. 1, the positive electrode lead 20 passes through a through hole in the insulating plate 18 and extends toward the sealing body 17, and the negative electrode lead 21 passes outside the insulating plate 19 and extends toward the bottom side of the outer casing 16. The positive electrode lead 20 is connected to the lower surface of an internal terminal plate 23 of the sealing body 17 by welding or the like, and a cap 27, which is a top plate of the sealing body 17 and is electrically connected to the internal terminal plate 23, serves as a positive electrode terminal. The negative electrode lead 21 is connected to the inner bottom inner surface of the outer casing 16 by welding or the like, and the outer casing 16 serves as a negative electrode terminal.
[0017] A gasket 28 is provided between the exterior can 16 and the sealing body 17 to ensure airtightness inside the battery. The exterior can 16 has a grooved portion 22 formed therein, with part of the side surface protruding inward, to support the sealing body 17. The grooved portion 22 is preferably formed in an annular shape along the circumferential direction of the exterior can 16, and supports the sealing body 17 on its upper surface. The sealing body 17 is fixed to the top of the exterior can 16 by the grooved portion 22 and the open end of the exterior can 16 which is crimped against the sealing body 17.
[0018] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cap 27 are laminated in this order from the electrode body 14 side. Each member constituting the sealing body 17 has, for example, a disk shape or a ring shape, and each member except the insulating member 25 is electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective centers, and the insulating member 25 is interposed between their respective peripheral edges. When the internal pressure of the battery increases due to abnormal heat generation, the lower valve body 24 deforms and breaks so as to push the upper valve body 26 toward the cap 27, thereby cutting off the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure further increases, the upper valve body 26 breaks, and gas is discharged from the opening of the cap 27.
[0019] The positive electrode 11, the negative electrode 12, and the separator 13 that constitute the electrode assembly 14, and in particular the positive electrode active material that constitutes the positive electrode 11, will be described in detail below.
[0020] [Positive electrode] The positive electrode 11 has a positive electrode core and a positive electrode composite layer provided on the surface of the positive electrode core. For the positive electrode core, a foil of a metal such as aluminum or an aluminum alloy that is stable in the potential range of the positive electrode 11, or a film with the metal disposed on the surface layer, can be used. The positive electrode composite layer contains a positive electrode active material, a conductive material, and a binder, and is preferably provided on both sides of the positive electrode core. The positive electrode 11 can be produced, for example, by applying a positive electrode composite slurry containing a positive electrode active material, a conductive material, and a binder, and then drying the coating, and compressing it to form a positive electrode composite layer on both sides of the positive electrode core.
[0021] Examples of the conductive material contained in the positive electrode mixture layer include carbon materials such as carbon black, acetylene black, ketjen black, and graphite. Examples of the binder contained in the positive electrode mixture layer include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide resins, acrylic resins, and polyolefin resins. These resins may be used in combination with cellulose derivatives such as carboxymethylcellulose (CMC) or its salt, and polyethylene oxide (PEO).
[0022] FIG. 2 is a schematic diagram showing a particle cross section of the positive electrode active material 30. As shown in FIG. 2, the positive electrode active material 30 is composed of at least one of a single particle 30A of a lithium transition metal composite oxide containing 85 mol % or more of Ni with respect to the total molar amount of metal elements other than Li, and a secondary particle 30B containing 10 or less primary particles 31. If the Ni content is 85 mol % or more, the capacity of the battery can be increased. On the other hand, if the Ni content is increased, the volume change of the positive electrode active material 30 accompanying charge and discharge becomes large, and particle cracking is likely to occur. As will be described in detail later, the positive electrode active material 30 achieves high capacity and high durability by improving the particle shape.
[0023] The lithium transition metal composite oxide preferably contains other metal elements in addition to Li and Ni. Examples of other metal elements include Co, Al, Mn, B, Mg, Ti, V, Cr, Fe, Cu, Zn, Ga, Sr, Zr, Nb, In, Sn, Ta, and W. Among these, it is preferable to contain at least Co and Al. For example, the lithium transition metal composite oxide may contain less than 10 mol% of Mn based on the total molar amount of metal elements excluding Li, and may not substantially contain Mn.
[0024] An example of a suitable lithium transition metal composite oxide is represented by the formula Li α Ni x Co y Al z O 2(wherein, 0.9≦α≦1.2, 0.85≦x≦0.95, 0.01≦y≦0.15, 0.01≦z≦0.10). As shown in the composition formula, it is preferable to set the upper limit of the Ni content to 0.95 mol %, and to add predetermined amounts of Co and Al. In this case, the crystal structure is stabilized, which contributes to improving durability.
[0025] The Li-site occupancy of the lithium transition metal composite oxide is preferably 80% or more, more preferably 90% or more, and particularly preferably 95% or more. If the Li-site occupancy is within this range, a high capacity can be realized. The Li-site occupancy means the proportion of Li occupying the Li sites in the crystal structure, and is determined by Rietveld analysis of the X-ray diffraction pattern of the lithium transition metal composite oxide. The Li-site occupancy may be 98% or more, or may be substantially 100%.
[0026] [Ratio of metal elements other than Li in the Li layer of lithium transition metal composite oxide] The ratio of metal elements other than Li present in the Li layer is determined by Rietveld analysis of the X-ray diffraction pattern obtained by X-ray diffraction measurement of the lithium transition metal composite oxide. The X-ray diffraction pattern is obtained by the powder X-ray diffraction method under the following conditions using a powder X-ray diffractometer (manufactured by Rigaku Corporation, product name "RINT-TTR", radiation source Cu-Kα).
[0027] Measurement range: 15-120° Scan speed: 4° / min Analysis range: 30-120° Background: B-spline Profile function: Split pseudo-Voigt function Constraint condition: Li(3a)+Ni(3a)=1 Ni(3a)+Ni(3b)=y (y is the Ni content in each element) ICSD No.:98-009-4814 In addition, the Rietveld analysis of the X-ray diffraction pattern is performed using the Rietveld analysis software PDXL2 (Rigaku Corporation).
[0028] In the positive electrode active material 30, the particle cross sections of the single particle 30A and the primary particle 31 have a polygonal shape including sides with a length of 1.5 μm or more, and at least three interior angles θ of the polygon are 45 to 160°. In other words, the positive electrode active material 30 is at least one of the single particle 30A consisting of one primary particle and the secondary particle 30B consisting of a small number of primary particles 31, 10 or less, and has a rough and angular outer shape. By making the particle shape like this, particle cracking is suppressed and durability is greatly improved.
[0029] The cross-sectional shape of the single particle 30A may be a polygonal shape having a side with a length of 1.5 μm or more and three or more interior angles θ of 45 to 160°, and may be a substantially quadrangular shape, a substantially pentagonal shape, a substantially hexagonal shape, or a polygonal shape having more angles. The length L of the longest side is, for example, 3 to 20 μm, and preferably 3 to 15 μm. In addition, in the single particle 30A, all of the interior angles θ may be 45 to 160°, 60 to 150°, or 70 to 130°, and there may be three or more interior angles θ of 90° or less.
[0030] The cross-sectional shape of the primary particles 31 constituting the secondary particles 30B may be a polygonal shape having sides with a length of 1.5 μm or more and three or more interior angles θ of 45 to 160°, similar to the single particles 30A, and may be a substantially quadrangular shape, a substantially pentagonal shape, a substantially hexagonal shape, or a polygonal shape having more angles. The length L of the longest side is, for example, 1.5 to 15 μm, and preferably 1.5 to 10 μm. In addition, in the primary particles 31, all of the interior angles θ may be 45 to 160°, 60 to 150°, or 70 to 130°, and there may be three or more interior angles θ of 90° or less.
[0031] In the particle cross-sectional shape (above polygonal shape) of the primary particle 31, for example, 20% or more of the sides are present on the surface of the secondary particle 30B and contact the voids in the positive electrode mixture layer. The voids in the positive electrode mixture layer are spaces present between particles of the positive electrode active material 30 (single particle 30A and secondary particle 30B). The secondary particle 30B does not include, for example, primary particles that are present only inside the particle and do not appear on the particle surface. In this case, at least a portion of all the primary particles 31 constituting the secondary particle 30B are present on the surface of the secondary particle 30B.
[0032] The average porosity of the single particles 30A is preferably 1% or less, more preferably 0.3% or less. The average porosity means the average ratio of voids in the single particles 30A, and is measured by the method described below. Similarly, the average porosity of the secondary particles 30B is preferably 3% or less, more preferably 2% or less. The single particles 30A and the secondary particles 30B are dense particles with few voids, and the average porosity may be less than 1%.
[0033] The average porosity of the single particles 30A and the secondary particles 30B is measured by the following method. (1) Using an ion milling device (for example, IM4000PLUS manufactured by Hitachi High-Technologies Corporation), a cross section of a positive electrode mixture layer including single particles 30A and secondary particles 30B is exposed. (2) A backscattered electron image of the cross section of the exposed positive electrode composite layer is taken using a scanning electron microscope (SEM). The magnification for taking the backscattered electron image is 1,000 to 10,000 times. (3) The SEM image of the cross section of the positive electrode mixture layer was imported into a computer and color-coded into two colors based on contrast using image analysis software, with the color with the lower contrast being designated as voids. (4) The void area of 100 single particles and secondary particles with a diameter of 2.5 μm or more randomly selected from the processed image is determined, and the ratio of the void area to the cross-sectional area of the particle (porosity) is calculated and averaged.
[0034] The positive electrode active material 30 may be substantially composed of single particles 30A only, or may be substantially composed of secondary particles 30B only, but is preferably a mixture of single particles 30A and secondary particles 30B. The ratio of the single particles 30A to the secondary particles 30B is not particularly limited, and the single particles 30A may be more, or the secondary particles 30B may be more. The positive electrode active material 30 may contain particles other than the single particles 30A and the secondary particles 30B within a range that does not impair the object of the present disclosure, but the content of the single particles 30A and the secondary particles 30B is preferably 50% by mass or more, more preferably 70% by mass or more, and particularly preferably 80% by mass or more.
[0035] The positive electrode mixture layer contains a positive electrode active material 30 as a main component. The content of the positive electrode active material 30 is preferably 90 mass% or more, and a suitable example is 90 to 98 mass% based on the mass of the positive electrode mixture layer. As described above, the positive electrode mixture layer preferably contains a conductive material and a binder. The contents of the conductive material and the binder are, for example, 0.5 to 5 mass% each based on the mass of the positive electrode mixture layer.
[0036] The BET specific surface area of the positive electrode mixture layer is 2.6 m before charging and discharging the battery. 2 / g or less. The BET specific surface area of the positive electrode mixture layer can be measured by peeling the positive electrode mixture layer from the positive electrode core and using a nitrogen adsorption / desorption BET specific surface area measuring device. The BET specific surface area of the positive electrode mixture layer is close to the BET specific surface area of the positive electrode active material 30, which is the main component. The positive electrode active material 30 is highly durable, so that the increase in the BET specific surface area is small even after charge / discharge cycles.
[0037] Fig. 3 is a particle cross-sectional image of the positive electrode active material taken by a scanning electron microscope (SEM). As shown in Fig. 3, the particles of the positive electrode active material, which is an example of the embodiment, have a rough and angular outer shape. The positive electrode active material also contains single particles with no grain boundaries within the particles, and secondary particles formed by agglomeration of a small number of primary particles. The cross-sectional shape of the majority of the particles constituting the positive electrode active material, for example, 80 mass % or more, is a polygonal shape including a side with a length of 1.5 μm or more and having three or more interior angles θ of 45 to 160°.
[0038] The positive electrode active material 30 can be synthesized by mixing a transition metal compound containing Ni and Co, an aluminum compound, and a lithium compound, baking the mixture at a high temperature, and then baking the mixture at a low temperature. The first baking is performed at a temperature 100 to 150°C higher than the baking temperature of a conventional general positive electrode active material, and the second baking is performed at a temperature 100 to 150°C lower than the first baking temperature, that is, at the baking temperature of a conventional general positive electrode active material. As a specific example of the baking temperature, the first baking temperature is 720 to 1000°C, and the second baking temperature is 600 to 800°C, and it is preferable that there is a temperature difference of 50°C or more between each baking step. In this case, a positive electrode active material 30 having a high Li site occupancy rate and consisting of angular particles is obtained.
[0039] [Negative electrode] The negative electrode 12 has a negative electrode core and a negative electrode composite layer provided on the surface of the negative electrode core. For the negative electrode core, a foil of a metal such as copper that is stable in the potential range of the negative electrode 12, a film with the metal disposed on the surface layer, or the like can be used. The negative electrode composite layer contains a negative electrode active material and a binder, and is preferably provided on both sides of the negative electrode core. The negative electrode 12 can be produced, for example, by applying a negative electrode composite slurry containing a negative electrode active material, a conductive material, a binder, and the like to the surface of the negative electrode core, drying the coating, and then compressing it to form a negative electrode composite layer on both sides of the negative electrode core.
[0040] The negative electrode mixture layer contains, as the negative electrode active material, for example, a carbon-based active material that reversibly absorbs and releases lithium ions. Suitable carbon-based active materials are graphites such as natural graphite, such as flake graphite, lump graphite, and earthy graphite, and artificial graphite, such as lump artificial graphite (MAG) and graphitized mesophase carbon microbeads (MCMB). In addition, the negative electrode active material may be a Si-based active material composed of at least one of Si and a Si-containing compound, or a carbon-based active material and a Si-based active material may be used in combination.
[0041] As the conductive material contained in the negative electrode mixture layer, carbon materials such as carbon black, acetylene black, ketjen black, and graphite can be used, as in the case of the positive electrode 11. As the binder contained in the negative electrode mixture layer, fluororesin, PAN, polyimide, acrylic resin, polyolefin, and the like can be used, as in the case of the positive electrode 11, but styrene-butadiene rubber (SBR) is preferably used. In addition, the negative electrode mixture layer preferably further contains CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof, polyvinyl alcohol (PVA), and the like. Among them, it is preferable to use SBR in combination with CMC or a salt thereof, and PAA or a salt thereof.
[0042] [Separator] A porous sheet having ion permeability and insulating properties is used for the separator 13. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. The material of the separator 13 is preferably a polyolefin such as polyethylene, polypropylene, a copolymer of ethylene and α-olefin, or cellulose. The separator 13 may have either a single-layer structure or a laminated structure. A heat-resistant layer containing inorganic particles, or a heat-resistant layer made of a highly heat-resistant resin such as an aramid resin, a polyimide, or a polyamideimide may be formed on the surface of the separator 13.
[0043] <Example> The present disclosure will be further described below with reference to examples, but the present disclosure is not limited to these examples.
[0044] <Example 1> [Synthesis of positive electrode active material] Lithium hydroxide and nickel-cobalt-aluminum composite oxide were mixed in a predetermined mass ratio, baked at 775°C for 30 hours, and then baked at 725°C for another 30 hours to obtain a composite oxide with the formula LiNi 0.88 Co 0.09 Al 0.03 O 2The resulting positive electrode active material was composed of single particles having a polygonal cross section including sides with a length of 1.5 μm or more, with at least three interior angles of the polygon being 45 to 160°, and secondary particles including 10 or less primary particles. The content of the single particles and secondary particles was estimated to be 90 mass % or more. The Li site occupancy rate of the resulting positive electrode active material was 98.9%, and the average porosity was 0.3%.
[0045] <Example 2> [Synthesis of positive electrode active material] Lithium hydroxide and nickel-cobalt-aluminum composite oxide were mixed in a predetermined mass ratio, baked at 750°C for 30 hours, and then baked at 700°C for another 30 hours to obtain a composite oxide with the formula LiNi 0.91 Co 0.045 Al 0.045 O 2 The resulting positive electrode active material was composed of single particles having a polygonal cross section including sides with a length of 1.5 μm or more, with at least three interior angles of the polygon being 45 to 160°, and secondary particles including 10 or less primary particles. The content of the single particles and secondary particles was estimated to be 90 mass % or more. The Li site occupancy rate of the resulting positive electrode active material was 98.5%, and the average porosity was 0.1%.
[0046] [Preparation of positive electrode] The above-mentioned lithium transition metal composite oxide was used as the positive electrode active material. The positive electrode active material, acetylene black, and polyvinylidene fluoride were mixed in a predetermined solid content mass ratio, and a positive electrode mixture slurry was prepared using N-methyl-2-pyrrolidone (NMP) as a dispersion medium. Next, the positive electrode mixture slurry was applied onto a positive electrode core made of aluminum foil, the coating was dried and compressed, and then cut into a predetermined electrode size to obtain a positive electrode.
[0047] [Preparation of negative electrode] A negative electrode composite slurry was prepared by mixing low BET graphite, a dispersion of styrene-butadiene rubber (SBR), and sodium carboxymethylcellulose (CMC-Na) at a predetermined solid content mass ratio, and using water as a dispersion medium. Next, this negative electrode composite slurry was applied to both sides of a negative electrode core made of copper foil, and the coating was dried and compressed, and then cut into a predetermined electrode size to produce a negative electrode in which a negative electrode composite layer was formed on both sides of the negative electrode core. Low BET graphite is a graphite having a volume per mass of 0.3 mm2 for pores with a pore diameter of 2 nm or less as determined by the DFT method from the nitrogen adsorption isotherm. 3 Graphite particles with a specific surface area of 1.5 m2 or less by the BET method. 2 / g or less.
[0048] [Preparation of non-aqueous electrolyte] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) were mixed in a predetermined volume ratio. LiPF 6 to obtain a non-aqueous electrolyte solution.
[0049] [Preparation of non-aqueous electrolyte secondary battery] The positive electrode with an aluminum positive electrode lead attached and the negative electrode with a nickel negative electrode lead attached were spirally wound with a polyethylene separator interposed therebetween and flattened to produce a wound electrode assembly, which was then housed in an exterior body made of aluminum laminate, and the nonaqueous electrolyte was injected into the exterior body, and the opening of the exterior body was sealed to produce a nonaqueous electrolyte secondary battery for evaluation.
[0050] [Durability evaluation of positive electrode active material] The fabricated battery was subjected to 1000 charge / discharge cycles under the following conditions, and then the battery was disassembled to measure the BET specific surface area of the positive electrode composite layer. The increase rate of the BET specific surface area was calculated by comparing it with the BET specific surface area of the positive electrode composite layer before and after charge / discharge. The evaluation results are shown in Table 1.
[0051] Charge / discharge conditions: In a temperature environment of 25°C, the battery was charged at a constant current of 0.5C up to a battery voltage of 4.1V, then recharged at 4.1V up to 0.02C, after which it was left to rest for 30 minutes and discharged at a constant capacity of 0.5E down to a battery voltage of 2.5V.
[0052] [Evaluation of battery capacity retention rate] The above charge / discharge cycle was repeated 1000 times in a temperature environment of 45° C., and the capacity retention rate was calculated by the following formula. The evaluation results are shown in Table 1.
[0053] Capacity retention rate = (discharge capacity after 1000 cycles / initial discharge capacity) x 100 <Comparative Example> In the synthesis of the positive electrode active material, a non-aqueous electrolyte secondary battery was produced in the same manner as in the example, except that the calcination was performed once, and the calcination conditions were 760°C and 3 hours, and the durability of the positive electrode active material and the capacity retention rate of the battery were evaluated (however, the number of charge / discharge cycles was changed to 600). The obtained positive electrode active material was composed of rounded secondary particles formed by agglomeration of many primary particles. The Li site occupancy rate of the obtained positive electrode active material was 99.5%, and the average porosity was 1.7%.
[0054] [Table 1]
[0055] As shown in Table 1, in the examples, the increase rate of the BET specific surface area of the positive electrode mixture layer after charge / discharge cycles is lower and the capacity retention rate of the battery is higher than in the comparative examples. As described above, the BET specific surface area of the positive electrode mixture layer is close to the BET specific surface area of the positive electrode active material, and the BET specific surface area increases due to cracking of the active material particles. Therefore, a low increase rate of the BET specific surface area means that particle cracking is suppressed and the durability of the positive electrode active material is high. Therefore, the positive electrode active material of the examples is less likely to cause particle cracking due to charge / discharge and has high durability compared to the positive electrode active material of the comparative examples. [Explanation of symbols]
[0056] 10 Nonaqueous electrolyte secondary battery 11 Positive electrode 12 Negative electrode 13 Separator 14 Electrode body 16 Outer can 17 Sealing body 18,19 Insulating plate 20 Positive lead 21 Negative lead 22 Grooved part 23 Internal terminal board 24 Lower valve body 25 Insulating materials 26 Upper valve 27 Cap 28 Gasket 30 Cathode active material 30A Single particle 30B Secondary particles 31 Primary particles
Claims
1. The lithium-transition metal composite oxide is composed of at least one of a single particle of the lithium-transition metal composite oxide containing 85 mol % or more of Ni with respect to the total molar amount of metal elements other than Li, and a secondary particle including 10 or less primary particles, The Li site occupancy rate of the lithium transition metal composite oxide is 80% or more, a particle cross section of the single particle and the primary particle has a polygonal shape including sides each having a length of 1.5 μm or more, and at least three interior angles of the polygon are 45 to 160°.
2. 2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein 20% or more of the sides of the primary particles are present on the surfaces of the secondary particles.
3. 3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the average porosity of the single particles and the secondary particles is 3% or less.
4. A positive electrode having a positive electrode core and a positive electrode mixture layer including the positive electrode active material according to any one of claims 1 to 3 provided on a surface of the positive electrode core; A negative electrode; A non-aqueous electrolyte; and a BET specific surface area of the positive electrode mixture layer before charging and discharging is 2.6 m 2 / g or less.
Citation Information
Patent Citations
Manufacture of positive active material and non-aqueous secondary battery
JP1997320601A
Spherical or pseudo-spherical positive electrode material of lithium ion battery, and manufacturing method and application thereof
JP2018045998A
Positive electrode active material for lithium secondary battery, method for producing the same, electrode including the same, and lithium secondary battery including the electrode
JP2020504416A
Positive electrode active material for lithium secondary battery and lithium secondary battery including the same
US20200083531A1
Positive electrode active material for non-aqueous electrolyte secondary battery
WO2018179916A1